Ductal metaplasia in esophageal submucosal glands is associated with inflammation and esophageal adenocarcinoma - Garman, Katherine S. (Histopathology, 2015)
AIMS: Recent studies have suggested that esophageal submucosal gland (ESMG) ducts harbor progenitor cells that may contribute to esophageal metaplasia. Our objective was to determine if histologic differences exist between the ESMGs of individuals with and without esophageal adenocarcinoma (EAC). METHODS AND RESULTS: We performed histologic assessment of 343 unique ESMGs from 30 control patients, 24 patients with treatment-naïve high-grade columnar dysplasia (HGD) or EAC, and 23 non-EAC esophagectomy cases. A gastrointestinal pathologist assessed H&E stained ESMG images using a scoring system that assigns individual ESMG acini to five histologic types (mucous, serous, oncocytic, dilated, or ductal metaplastic). In our model, ductal metaplastic acini were more common in patients with HGD/EAC with 12.7% and 3.5% in controls (p=0.006). We also identified greater proportions of acini with dilation (21.9%, p<0.001) and, to a lesser extent, ductal metaplasia (4.3%, p=0.001) in non-EAC esophagectomy cases versus controls. Ductal metaplasia tended to occur in areas of mucosal ulceration or tumor. CONCLUSIONS: We found a clear association between ductal metaplastic ESMG acini and HGD/EAC. Non-EAC cases had dilated acini and some ductal dilation. Because ESMGs and ducts harbor putative progenitor cells, these associations could have significance for the understanding the pathogenesis of EAC.